Antibiotic resistance patterns of staphylococcus aureus in chicken farms: Implications for health resilience in Indonesia - Tiara Rahayu; M Ridhwan Amarullah; Alexander Yabansabra; Aparna Dixit; Muhamad Syazali; Nabila Swarna Puspa Hermana (FoundAE, 2023)
Health resilience refers to an individual's or a community's ability to withstand and recover from various health challenges and crises. Antibiotic resistance poses a significant threat to health resilience due to its impact on the effectiveness of antibiotics. The urgency of the issue of multidrug bacterial resistance in public health is a concern. The phenomenon discussed in this paper is related to the environment that becomes resistant to the antibiotic Staphylococcus aureus which causes high morbidity and mortality in animals such as chickens. In this study, there were three levels of antibiotic resistance based on clear zone media culture, namely resistance, intermediates, and sensitivity with each antibiotic totaling nine chicken cloacal swab samples. The purpose of this study was to determine the pattern of the significance of antibiotic resistance in S. aureus in three chicken farms in West Java Province (Bogor, Parung, and Sukabumi). This study used secondary data from previous studies and analyzed with nonparametric statistical methods using the Kruskal Wallis Test (One Way ANOVA). The results of the analysis showedalmost all gave a resistant response characterized by the absence of a clear zone in bacterial culture media treated with the same antibiotic in all chicken cloaca swab samples taken from farms in Bogor, Parung, and Sukabumi. Thus, resulting in the same resistance pattern. This indicates the pattern of the resilience of resistance in West Java is the same because the ecological conditions and living standards of the community are almost the same. These results may illustrate important concerns for the possibility of other regions in Indonesia having similar patterns of antibiotic resistance, so antibiotic use must adhere to appropriate guidelines to combat further antibiotic-resistant strains.